Antidiarrheal Activity of Water Extracts of Guava Leaves (Psidium guajava L.) and Water Extracts of Green Tea Leaves (Camellia sinensis L.) Combination in Swiss Webster Mice - Dewi, Puspa Sari; Sutjiatmo, Afifah B.; Nurdiansyah, Arif (Acta Pharmaceutica Indonesia, 2013)
The antidiarrheal activities of water extracts of guava leaves (Psidium guajava L.) and water extracts of green tea leaves (Camellia sinensis L.) combination against castor oil-induced diarrhea and intestinal transit time method have been determined in Swiss Webster male mice. Twenty five male Swiss Webster mice weighing around 20-35 g were divided randomly into 5 groups for each method. The first group as a control was given gom 2% po, the second group was treated with loperamide hydrochloride 0.52 mg/kg body weight po. The third, fourth and fifth groups were treated with water extract of guava leaves (G) and water extract of green tea leaves (T) combinations i.e. (G : T) 112.5 : 110.55 ; (G : T ) 75 : 221.1 and (G : T) 37.5 : 331.65 mg/kg BW respectively. The results showed that all extract combinations had antidiarrheal activities, significantly differences in increased stool consistency, stool weight, onset and diarrhea duration, and intestinal transit time in mice that has been given extract compared to those of control group. Frequency of defecacy of mice administered by water extract of (G : T) 75 : 221.1 at minute 180-240 showed effects equal to the comparison group and significantly different compared to that of control group (p<0.05). Combination water extract of guava leaves 75 mg/kg BW and water extract of green tea leaves 221.1 mg/kg BW was the best combinations in this research.Keywords: intestinal transit time method, oleum ricini-induced, water extracts, guava leaves, green tea leavesÂ AbstrakPada penelitian ini dilakukan penentuan aktifitas antidiare dari kombinasi ekstrak air daun jambu biji (Psidium guajava L.) dan ekstrak air daun teh hijau (Camellia sinensis L.) dengan menggunakan metode induksi dengan minyak jarak dan melihat waktu singgah pada saluran cerna. Penelitian ini menggunakan 25 jantan galur Swiss Webster dengan bobot berkisar antara 20-35 g yang dibagi menjadi 5 kelompok untuk setiap metode. Kelompok pertama diberi gom 2% secara peroral (po) sebagai kelompok kontrol, kelompok kedua diberi loperamid hidroklorida 0,52 mg/kg berat badan secara peroral. Kelompok ketiga, keempat dan kelima masing-masing diberi kombinasi ekstrak air daun jambu biji (G) dan ekstrak air daun teh hijau (T) dengan perbandingan sebagai berikut (G:T) 112,5 : 110,55 ; (G:T ) 75 : 221,1 dan (G:T) 37,5 : 331,65 mg/kg BB. Hasil penelitian menunjukkan bahwa seluruh ekstrak memiliki aktifitas antidiare, terdapat perbedaan yang signifikan pada konsistensi feses, berat feses, onset dan durasi diare, dan pada waktu singgah saluran cerna antara mencit yang diberi ekstrak dan mencit pada kelompok kontrol. Frekuensi dari defekasi pada mencit yang diberi ekstrak air (G : T) 75 : 221,1 pada menit ke 180-240 menunjukkan adanya efek yang serupa dengan kelompok pembanding dan memiliki perbedaan yang bemakna dengan kelompok kontrol (p<0,05). Kombinasi antara ekstrak air daun jambu biji 75 mg/kg BB dan ekstrak air daun the hijau 221,1 mg/kg BB merupakan kombinasi yang paling baik dalam penelitian ini.Kata kunci : Metode waktu singgah saluran cerna, induksi oleum ricini, ekstrak air, daun jambu biji, daun teh hijau.